Perbandingan Pengaruh Ekstrak Buah Naga Merah dan Ekstrak Bunga Mawar Merah Terhadap Sel Surya - Damayanti, Septia Ayu Nisitta; , Hasyim Asy'ari, ST.MT (2016)
As more dense population of the earth, the demand for and use of earth energy will increasingly inflated rapidly and that makes human beings to develop new energy sources such as solar energy. Solar energy is one of the energy currently being developed because it has the advantage that no consumables and pollution free. To utilize electrical energy can not be directly due to be changed form the electrical energy. Before harnessed the energy of light must be converted into electrical energy, to convert require equipment such as solar cells. To maximize the solar energy needs to increase the efficiency of solar cells. The purpose of this research was to compare the effect of red dragon fruit extract and extract of red roses on solar cells. The method used in this study by soaking the red dragon fruit and red roses with a solution - a solution like HCl 10%, citric acid, and ethanol. Then applied it the surface of the solar cell and observe the value of output voltage and current. The results showed that the difference between the highest value generated in the citric acid bath 5 days with a value of 0,2336905%. However, the minimum efficiency of 0,0345197% is the lowest efficiency that uses a red dragon fruit extract with 10% HCL solution were soaked for two days compared with the situation ekstak red roses with citric acid soaked for two days. In addition to the effect of extracts of the output of the panel is also influenced by the high light intensity, the higher the intensity of sunlight, the output value will be higher.